Canada. IICA strategy 2014-2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
The IICA Office in Canada for the 2014-2018 Programming period will be playing an important role in packaging and sharing best practices, policies and regulations as well as required technologies as these relate to the 4 Flagship Projects and Agricultural Health and Food Safety. In addition, projects and identified project activities will be facilitated primarily in the Flagship Project for Agricultural Chains and Resilience and Risk Management in Agriculture. Notwithstanding this, technical assistance requests from Latin America and the Caribbean will be serviced based on identified competencies in Canada. In this, as well as cross thematic areas such as youth, gender balance and private sector engagement, it is anticipated that regional initiatives will complement local activities.